2016
DOI: 10.1016/j.physletb.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of holographic entanglement entropy in massive gravity

Abstract: The phase structure of holographic entanglement entropy is studied in massive gravity for the quantum systems with finite and infinite volumes, which in the bulk is dual to calculate the minimal surface area for a black hole and black brane respectively. In the entanglement entropy$-$temperature plane, we find for both the black hole and black brane there is a Van der Waals-like phase transition as the case in thermal entropy$-$temperature plane. That is, there is a first order phase transition for the small c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 23 publications
1
67
1
2
Order By: Relevance
“…It was found that the entanglement entropy can characterize the related phase transition for a charged AdS black hole. Further studies on holographic entanglement entropy and its relation to phase transition have been done for various AdS black holes in [35][36][37][38]. For the AdS phantom black hole presented in this paper, we will further show such a relation which keeps valid even for the case with the Ricci flat horizon black hole.…”
Section: Introductionmentioning
confidence: 59%
“…It was found that the entanglement entropy can characterize the related phase transition for a charged AdS black hole. Further studies on holographic entanglement entropy and its relation to phase transition have been done for various AdS black holes in [35][36][37][38]. For the AdS phantom black hole presented in this paper, we will further show such a relation which keeps valid even for the case with the Ricci flat horizon black hole.…”
Section: Introductionmentioning
confidence: 59%
“…It was pointed out that for this phase transition, the maximal tunnelling current and the coherence length of junction are affected by the mass of graviton in Vegh's massive gravity model [67]. In addition, phase transition of holographic entanglement entropy in this massive gravity is investigated as well [68]. It is also notable that the existence of massive graviton results into new phenomenology for gravitational system.…”
Section: Jhep05(2016)029mentioning
confidence: 96%
“…Especially, making use of entanglement entropy, Johnson [22] proposed that the Van der Waals-like phase transition can be illustrated in the entanglement entropy-temperature plane. Now, the related work has been generalized to massive gravity [23] and Weyl gravity [24], as well as supergravity spacetime [25]. Furthermore, the equal area construction has also been verified in the entanglement entropytemperature plane [26].…”
Section: Introductionmentioning
confidence: 92%